Early Life Adverse Environmental Exposures Increase the Risk of Uterine Fibroid Development: Role of Epigenetic Regulation - Yang, Qiwei; Diamond, Michael P.; Al-Hendy, Ayman (Frontiers in Pharmacology, 2016)
Uterine Fibroids (UF(s), AKA: leiomyoma) are the most important benign neoplastic threat to women’s health. They are the most common cause of hysterectomy imposing untold personal consequences and hundreds of billions of healthcare dollars, worldwide. Currently, there is no long term effective FDA-approved medical treatment available, and surgery is the mainstay. The etiology of UFs is not fully understood. In this regard, we and others have recently reported that somatic mutations in the gene encoding the transcriptional mediator subunit Med12 are found to occur at a high frequency (~85%) in UFs. UFs likely originate when a Med12 mutation occurs in a myometrial stem cell converting it into a tumor-forming stem cell leading to a clonal fibroid lesion. Although the molecular attributes underlying the mechanistic formation of UFs is largely unknown, a growing body of literature implicates unfavorable early life environmental exposures as potentially important contributors. Early life exposure to endocrine disrupting compounds (EDCs) during sensitive windows of development can reprogram normal physiological responses and alter disease susceptibility later in life. Neonatal exposure to the EDCs such as diethylstilbestrol (DES) and genistein during reproductive tract development has been shown to increase the incidence, multiplicity and overall size of UFs in the Eker rat model, concomitantly reprogramming estrogen-responsive gene expression. Importantly, EDC exposure represses enhancer of zeste 2 (EZH2) and reduces levels of histone 3 lysine 27 trimethylation (H3K27me3) repressive mark through Estrogen receptor / Phosphatidylinositide 3-kinases / Protein kinase B non-genomic signaling in the developing uterus. Considering the fact that distinct Mediator Complex Subunit 12 (Med12) mutations are detected in different fibroid lesions in the same uterus, the emergence of each Med12 mutation is likely an independent event in an altered myometrial stem cell. It is therefore possible that a chronic reduction in DNA repair capacity eventually causes the emergence of mutations such as Med12 in myometrial stem cells converting them into fibroid tumor-forming stem cells, and thereby leads to the development of UFs. Advancing our understanding of the mechanistic role epigenetic regulation of stem cells plays in mediating risk and tumorigenesis will help in pointing the way towards the development